2014
DOI: 10.1186/1471-2466-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study for early supported discharge in adults with respiratory infection in the UK

Abstract: BackgroundMany patients with pneumonia and lower respiratory tract infection that could be treated as outpatients according to their clinical severity score, are in fact admitted to hospital. We investigated whether, with medical and social input, these patients could be discharged early and treated at home.Objectives: (1) To assess the feasibility of providing an early supported discharge scheme for patients with pneumonia and lower respiratory tract infection (2) To assess the patient acceptability of a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These factors included the need for clarity on the ESD model of care, the need for some flexibility in the application of ESD criteria, the need for advance planning of discharge from ESD, the need for person-centred ESD scheduling and the need for ESD HCPs to work effectively as an interprofessional team. Evidence is emerging of the effectiveness of ESD with other populations such as people with chronic obstructive pulmonary disorder (COPD), and post orthopaedic surgery, respiratory infections and for the older person [ 79 84 ]. Therefore, our findings on organisational and logistical factors that supported the success of ESD may be applicable to these services also such as the need for interprofessional practice and clarity on the model of care.…”
Section: Discussionmentioning
confidence: 99%
“…These factors included the need for clarity on the ESD model of care, the need for some flexibility in the application of ESD criteria, the need for advance planning of discharge from ESD, the need for person-centred ESD scheduling and the need for ESD HCPs to work effectively as an interprofessional team. Evidence is emerging of the effectiveness of ESD with other populations such as people with chronic obstructive pulmonary disorder (COPD), and post orthopaedic surgery, respiratory infections and for the older person [ 79 84 ]. Therefore, our findings on organisational and logistical factors that supported the success of ESD may be applicable to these services also such as the need for interprofessional practice and clarity on the model of care.…”
Section: Discussionmentioning
confidence: 99%
“…This diagnostic imprecision has important implications for the use of NW sampling as a diagnostic technique since it would lead to many inappropriate samples being collected. We have previously demonstrated that confusion is common in LRTI patients (>20%) ( 19 ). The rates of LRTI increase with age (63% of the patients admitted with CAP were aged >65 years and 25% were ≥85 years old) ( 20 ) as do the rates of comorbidities (including dementia); therefore, recent hospital admission is also common.…”
Section: Discussionmentioning
confidence: 99%
“…Early discharges in other infectious disease, such as pneumonia, have shown promise in increasing patient satisfaction and reducing readmissions and hospital-acquired infections. 10…”
Section: Discussionmentioning
confidence: 99%